Variability for seed longevity among advanced breeding lines of soybean (Glycine max) - S.K. LAL; S.K. JAIN; K.P. SINGH; AKSHAY TALUKDAR; R.L. SAPRA (Seed Research, 2026)
The correlation between results of field emergence and accelerated aging test (0.664*) and the correlation between accelerated seed ageing and grain yield kg/ha (0.745*) were highly significant in the advanced soybean breeding lines tested. The genotypes showing more than 90% germination under accelerated aging test yielded more than 20 q/ha, whereas the genotypes which exhibited poor germination (